Integrated multivariate analysis to identify superior cowpea genotypes - Dos Santos, Adriano; Ceccon, Gessí; Davide, Livia Maria Chamma; Luiz Neto Neto, Antonio; Silva, Juslei Figueiredo da; Alvares, Rita de Cássia Félix (Comunicata Scientiae, 2016)
Genetic divergence among 40 cowpea genotypes was quantified by means of integrated multivariate analysis aiming to assist the selection and development of new cultivars. The experiment was carried out in randomized blocks design with 40 treatments and 4 repetitions. The multivariate techniques applied were partially concordant, following the same trend for clustering of genotypes. Directed crosses between the genotypes belonging to group I with group IV and VI will be able to lead to the creation of segregating families with high yield potential and an increase in probability of recovering individuals. The variables of hundred grain weight, average pod length and number of seeds per pod are the main determinants in quantification of the genetic divergence among cultivars.